Real-time effective density monitor (DENSMO) for aerosol nanoparticle production. Issue 5 (3rd May 2016) - Juuti, Paxton; Arffman, Anssi; Rostedt, Antti; Harra, Juha; Mäkelä, Jyrki M.; Keskinen, Jorma
ABSTRACT: A new instrument, density monitor (DENSMO), for aerosol particle size distribution characterization and monitoring has been developed. DENSMO is operationally simple and capable of measuring the effective density as well as the aerodynamic and the mobility median diameters with a time resolution of 1 s, from unimodal particle size distributions. The characterization is performed with a zeroth order mobility analyzer in series with a low pressure impactor and a filter stage. The operation of DENSMO was investigated with sensitivity analysis and, based on the results, optimal operation parameters were determined. DENSMO was also compared, in lab test measurements, against a reference method with several particle materials with bulk densities from 0.92 to 10.5 g/cm 3 . The results show that the deviation from the reference method was less than 25% for suitable materials. Copyright © 2016 American Association for Aerosol Research